Trends in Inflammatory Bowel Disease Therapy: A Meta-Analytic Approach - Gregory W Whiting; Joseph Lau; Bruce Kupelnick; Thomas C Chalmers (Canadian Journal of Gastroenterology)
OBJECTIVE: To illustrate the current meta-analytic approach to extracting clinically useful information from the glut of randomized controlled trials (RCTs) of the treatment of acute attacks of Crohn's disease.